The Impact of Standardized Teaching Methodologies on Student Learning and Teacher Autonomy in Ghanaian Schools - Fenuku, Samson Dodzi; Akpaku, Ernest (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
This study examines the impact of standardized teaching methodologies on student learning and teacher autonomy within the Ghanaian educational context. A mixed-methods approach was employed, integrating quantitative analysis of student performance data from standardized tests with qualitative insights gleaned from semi-structured interviews and classroom observations of teachers and administrators, alongside a broader survey of teacher perceptions. Quantitative findings indicated that standardized teaching methodologies were associated with improved student performance on standardized assessments. However, qualitative data revealed a complex landscape where teacher autonomy and the ability to provide culturally relevant instruction were seen as potentially compromised by the structure of standardized curricula. The study's qualitative themes highlighted the dual-edged nature of standardization, with teachers expressing a need for both the guidance and constraints that standards provide. Professional development emerged as a critical factor, with teachers seeking ongoing support to effectively implement standardized teaching methodologies. The research underscores the importance of balancing the clarity and structure of standardized teaching with the flexibility necessary for teachers to meet the diverse needs of their students. It also emphasizes the need for culturally responsive teaching practices and the provision of continuous professional development opportunities for teachers. It suggests that while standardized teaching can enhance student performance, it must be implemented in a manner that supports teacher autonomy, adaptability, and professional growth to achieve the best outcomes for all students.